Service robots and robotics : design and application - Ceccarelli, Marco; Zielinska, Teresa; Ding, Xilun; Chen, Hao; Xu, Kun; Dai, Jian S.; Xidias, Elias K.; Aspragathos, Nikos A.; Azariadis, Philip N.; Bandyopadhyay, Sandipan; Cabanes, Itziar; Kawano, Alexandre; et al. (Premier reference source, 2012)
"This book offers the latest research within the field of service robotics, using a mixture of case studies, research, and future direction in this burgeoning field of technology"--Provided by publisher.